Relationships Between Identity, Well-Being, and Willingness to Sacrifice in Personal and Collective Favorite Places: The Mediating Role of Well-Being - Knez, Igor; Eliasson, Ingegärd; Gustavsson, Eva (Frontiers in Psychology, 2020)
In line with research indicating positive relationships between personal and collective people-place bonding and well-being, and that collectivistic compared to individualistic commitment may have stronger associations with pro-environmental behavior, we investigated relationships between identity, well-being, and willingness to sacrifice (type of pro-environmental behavior) in personal and collective favorite places. A total of 884 respondents, living in three Swedish municipalities, participated in this study. In line with the hypotheses, we showed congruent positive relationships between place-related: (1) personal identity and personal well-being; (2) collective identity and collective well-being, (3) collective identity and collective willingness to sacrifice; and (4) an incongruent positive association between collective identity and personal willingness to sacrifice. Additionally, a significant role of well-being in mediating the identity → willingness to sacrifice relationship was reported, suggesting that our willingness to pay much higher taxes and prices and to accept cuts in standard of living in order to protect our personal and collective favorite places might be accounted for partly by how we feel visiting these places.